Designing Emotionally Sentient Agents - McDuff, Daniel; Czerwinski, Mary (Communications of the ACM, 2018)
Today, people increasingly rely on computer agents in their lives, from searching for information, to chatting with a bot, to performing everyday tasks. These agent-based systems are our first forays into a world in which machines will assist, teach, counsel, care for, and entertain us. While one could imagine purely rational agents in these roles, this prospect is not attractive for several reasons, which we will outline in this article. The field of affective computing concerns the design and development of computer systems that sense, interpret, adapt, and potentially respond appropriately to human emotions. Here, we specifically focus on the design of affective agents and assistants. Emotions play a significant role in our decisions, memory, and well-being. Furthermore, they are critical for facilitating effective communication and social interactions. So, it makes sense that the emotional component surrounding the design of computer agents should be at the forefront of this design discussion.